Assessment of Genetic Parameters for Seed Cotton Yield Related Traits and Biochemical Parameters in Desi Cotton (Gossypium arboreum L.) - Vekariya, R. D.; Nimbal, S.; batheja, Aashima; Prakash, Jay; Patel, C. S.; Singh, A. G. (International Journal of Bio-resource and Stress Management, 2017)
Desi cotton Gossypium arboreum has wide adaptability under rainfed situation and also high degree of resistance to biotic and abiotic stresses. Present investigation total sixty GMS based desi cotton F1 hybrids along with complete set of nighteen parents and one checks were evaluated for variability, heritability and genetic advance in different yield and yield contributing traits. The treatment, i.e. mean sum of squares due to genotypes revealed significant differences for all characters studied, that revealing the presence of high genetic variability among the genotypes. The estimates of GCV were lower than the respective PCV; it means that the apparent variation is not only due to genotypes but also due to the influence of environmental factors on the expression of the traits studied. Characters like seed cotton yield/plant, No. of bolls plant-1 and gossypol content showed high GCV, PCV, heritability coupled with high genetic advance as percent of mean, suggesting that selection for the improvement of these characters may be rewarding. High heritability estimates coupled with high expected genetic advance as percent mean were observed for the traits like, seed cotton yield plant-1, No. of bolls plant-1 and gossypol content, that indicating presence of additive gene effects in its inheritance and such characters could be improved by selection. Low heritability estimates with expected low genetic advance were observed for the traits like Lint index, boll weight boll-1 and seed index that also indicates greater role of non-additive gene action in their inheritance suggesting heterosis breeding could be useful for improving these traits.